Unleashing the SAVI Learning Model: Enhancing Grade IV Science Outcomes: Mengoptimalkan Hasil Belajar Kognitif pada Ilmu Pengetahuan Kelas IV: Mengungkap Potensi Model Pembelajaran SAVI - Manzilatun Nimah; Akhtim Wahyuni (Universitas Muhammadiyah Sidoarjo, 2023)
This quantitative research aimed to investigate the impact of the SAVI (Somatic, Auditory, Visual, and Intellectual) learning model on the cognitive learning outcomes of fourth-grade students in science at Ash-Shiddiqiyah Elementary School. The study employed an experimental design with a pre-test and post-test approach. The results revealed a significant improvement in students' cognitive learning outcomes, as evidenced by a t-test value of 18.589, surpassing the critical t-value of 2.131. The calculated effect size (eta squared) of 0.95 indicated a substantial influence of the SAVI learning model on the students' science learning outcomes. These findings have important implications for educators and policymakers, highlighting the potential of innovative teaching methodologies to enhance students' academic achievements in science education. Highlights: The study examines the impact of the SAVI learning model on cognitive learning outcomes in Grade IV Science. The experimental design employed a pre-test and post-test approach to evaluate the effectiveness of the SAVI learning model. The findings indicate a significant improvement in academic achievement, emphasizing the potential of innovative teaching methodologies. Keywords: Cognitive learning outcomes, Grade IV Science, SAVI learning model, Experimental design, Academic achievement.